2022
DOI: 10.1039/d2fo01042a
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endoplasmic reticulum stress-associated pathways and hepatocyte apoptosis participates in the attenuation of betulinic acid on alcohol-provoked liver injury in mice

Abstract: BA protects against alcohol-induced liver damage through the alleviation of oxidative stress and suppression of ERS-induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…There is evidence that ERS participates in the occurrence and development of various liver disorders, including fatty liver, ischemia–reperfusion injury, liver fibrosis and DILI 38–41 . Moreover, evidence has suggested that activation of ERS and apoptosis could cause liver injury, 42 which is consistent with our previous findings in LO2 cells after CTD intervention 8 . Furthermore, suppressing three branches of the ERS signalling pathway could alleviate DILI 43 …”
Section: Discussionsupporting
confidence: 88%
“…There is evidence that ERS participates in the occurrence and development of various liver disorders, including fatty liver, ischemia–reperfusion injury, liver fibrosis and DILI 38–41 . Moreover, evidence has suggested that activation of ERS and apoptosis could cause liver injury, 42 which is consistent with our previous findings in LO2 cells after CTD intervention 8 . Furthermore, suppressing three branches of the ERS signalling pathway could alleviate DILI 43 …”
Section: Discussionsupporting
confidence: 88%